Religion, pluralism, the common good and poverty - Boesak, Allan (Nederduitse Gereformeerde Teologiese Tydskrif, 2012)
Poverty is a scourge that threatens the common good. This contribution analyses situations of poverty in South Africa as well as globally and seeks to explore the ways in which the shared values of the three Abrahamic religions which feature strongly in South Africa, can address this situation. The author does not plead for a blend of these religions, but instead for a search of those values at once shared by and unique to each that can make a contribution to the common search for justice in a pluralistic society such as ours and thereby serve the common good.